EFFECT OF AGRICULTURE SITES AND GROWTH STAGES ON PHYSICAL AND CHEMICAL PROPERTIES ON DATE PALM Phoenix - Abdul-Wahed, M.Sh. (University of Thi-Qar Journal of Science, 2012)
This study was conducted in three sites of basrah fields (Hartha, Shutt Al-Arab and Abu-Alkhasseb , during the growing season 2002 , to vestigated the agriculture site on physical and chemical properties of date palm fruits cv . khentar at the Chemri ,Khalal and Rutab stages ,The results showed that the site was had a significant effect on physical and chemical properties of date palm cv. Khentar .So the statistical analysis results showed that there were a significant difference among sites in physical and chemical properties of date palm fruit in Abu-Alkhaseb site had significant effect compaire with other sites.